Effectiveness of the Volunteer Teaching From Home Program in Welcoming Education in the Era 5.0 - Antin Rista Yuliani; Wulandari, Catur (Journal of Indonesian Progressive Education, 2024)
Education in the current era is often referred to as modern education. This means that education cannot be separated from the role of information and communication technology. Meanwhile, if you look at the current situation and conditions of Indonesia, it is being attacked by an epidemic which is affecting several aspects of life. One of them is in the educational aspect. The presence of this epidemic seems to give us "shock therapy" from the beginning we could carry out our activities easily, but now everything is restricted. The teaching and learning process also experienced a transformation. Initially students studied face to face, now they have changed online or online. The online learning process certainly creates certain challenges, not only for students or teachers but also for parents. Especially for students who live in remote areas with minimal infrastructure. With the presence of these challenges, Indonesian people are required to play a role in helping to minimize this problem, especially the younger generation. One thing that can be done is to participate in the Teach From Home volunteer program. This research examines the concepts promoted in the Teaching From Home volunteer program, what its role is in alleviating online learning problems, and how effective this program is in welcoming education in the 5.0 era. Meanwhile, the subjects of this research were elementary school/equivalent students who were affected by Covid-19. Thus, this research will be useful for teachers or educators so that they get an idea of ​​preparing for the presence of education in the 5.0 era. This research uses qualitative research methods.